Thorium: Crustal abundance, joint production, and economic availability. (June 2015) - Jordan, Brett W.; Eggert, Roderick G.; Dixon, Brent W.; Carlsen, Brett W.
Abstract: Recently, interest in thorium׳s potential use in a nuclear fuel cycle has been renewed. Thorium is more abundant, at least on average, than uranium in the earth׳s crust and, therefore, could theoretically extend the use of nuclear energy technology beyond the economic limits of uranium resources. This paper provides an economic assessment of thorium availability by creating cumulative-availability and potential mining-industry cost curves, based on known thorium resources. These tools provide two perspectives on the economic availability of thorium. In the long term, physical quantities of thorium likely will not be a constraint on the development of a thorium fuel cycle. In the medium term, however, thorium supply may be limited by constraints associated with its production as a by-product of rare earth elements and heavy mineral sands. Environmental concerns, social issues, regulation, and technology also present issues for the medium and long term supply of thorium. Abstract : Highlights: Joint production is a more important availability factor than crustal abundance. Thorium as a by-product of titanium and rare earth mining is the lowest cost source. Thorium availability depends heavily on titanium and rare earth markets. Estimated thorium resources could power nearly 400 GWe of capacity for centuries.